AN ASSESSMENT OF THE COVID-19 PANDEMIC IN SOUTH AFRICA:: FROM ITS IMPACT ON THE ECONOMY TO THE REBUILDING STRATEGY - Mandlazi, Mario; Nyasha, Sheilla (Annals of Spiru Haret University. Economic Series, 2024)
The conventional understanding is that the coronavirus pandemic (Covid-19) has challenged the development of the economies at all levels – global, regional and domestic. The need to assess its damage to the South African economy became imperative if the economy has to be resuscitated in an informed and targeted way. The study therefore aimed at assessing the impact of the Covid-19 Pandemic in South Africa, assessing the effectiveness of the South African government response to Covid-19 and outlining government strategies that have been employed in an effort to rebuild the South African economy. The study utilised the qualitative research approach in which semi-structured interviews were used to collect information on a purposive sample of 12 participants. Through the use of thematic analysis as the data analysis method, the study discovered that the Covid-19 pandemic has both long-term and short-term impacts on the South African economy such as loss of employment, contracting GDP, depressed growth below pre-pandemic projections and lack of organisational performance. In response to Covid-19, the government introduced supporting programmes to businesses, regulations aimed at allowing credit facilities and partnership with various stakeholders. Strategies such as expansionary monetary strategies and the introduction of specific programmes targeting the resuscitation of key economic sectors have been implemented to rebuild the economy. The study, therefore, recommends that the government needs to build a buffer of resources in preparation of devastating pandemics such as Civid-19, such that when the country is hit by the pandemic, there are avenues that can be explored to resuscitate the economy. There is also need to ensure that there is a platform where business organisations can flourish as they can access capital and resources.